AUTOMATION AND ROBOTICS IN LIGHT INDUSTRY PRODUCTION LINES (International journal of artificial intelligence, 2025)
The rapid advancement of automation and robotics has significantly transformed the light industry, particularly the textile and garment sectors. With the growing demand for efficiency, accuracy, and sustainability, companies are increasingly adopting automated production lines and robotic systems to replace labor-intensive processes. This article explores the theoretical foundations, current applications, challenges, and future prospects of automation and robotics in light industry. Emphasis is placed on smart factories, digital integration, and Industry 4.0 principles. Furthermore, the study highlights the socio-economic impacts of automation, such as workforce transformation, skill development, and productivity growth. Graphs and tables are provided to illustrate comparative efficiency gains, energy savings, and defect reduction in automated versus traditional production systems. The results suggest that a gradual but consistent integration of robotics leads to significant improvements in product quality, cost-effectiveness, and environmental sustainability.